“I feel like some students are better connected”: Students’ perspectives on applying for extracurricular partnership opportunities - Marquis, Elizabeth; Jayaratnam, Ajitha; Mishra, Anamika; Rybkina, Ksenia (International Journal for Students as Partners, 2018)
While existing research has discussed the need for student-faculty partnership opportunities to be inclusive and accessible, attention to students’ motivations for participating in extracurricular partnership activities, and to their sense of the relative accessibility of such opportunities, has been limited. The present study, designed and conducted by students and faculty working in partnership, aimed to address this gap in the literature by exploring how students at a Canadian research-intensive university with a centrally-supported Student Partners Program perceive extracurricular partnership opportunities and the process of applying for them. Drawing from survey and focus group data, we describe students’ motivations for taking part in student-staff partnership initiatives and their sense of the program features that enable and constrain students’ participation. Implications of these findings for practitioners and researchers interested in Students as Partners are discussed.